LONG TERM RESULTS OF SURGICAL TREATMENT FOR BREAST CANCER - Hasan Karanlık; Vahit Özmen; Oktar Asoğlu; Abdullah İğci; Mustafa Keçer; Sıtkı Tuzlalı; Mahmut Müslümanoğlu; Işık Aslay; Erkan Topuz (European Journal of Breast Health, 2006)

(untitled)
BACKGROUND: Although many clinical data regarding breast cancer treatment have already been reported in the literature, few clinical data with long term follow up results have been reported from Turkey. The objective of the current study is to determine the long term results of surgical treatment in early stage breast cancer.METHODS: We reviewed the records of 1841 patients with stage I and II invasive breast cancer who underwent mastectomy or breast conserving surgery (BCS) at our institution between January 1989 and January 2005. The association of clinico-pathological features and treatment modalities with overall survival, disease free survival and local recurrences were investigated.RESULTS: The median follow up period was 76 months (2-192 months). The mastectomy group, 1209 patients (66%), was compared with the BCS group, 632 patients (34%). Five year disease free and overall survival rates were 77% and 85% for patients with mastectomy, 78% and 86% for patients with BCS, respectively. The 5 year local recurrence rate was 4% for mastectomy group and 6% for BCS group. Multivariate logistic regression analyses showed that age below 40 years (p=0.02) and boost radiation therapy (p=0.03) were significant risk factors for local recurrence in BCS.CONCLUSİONS: There are no significant differences in overall or dissease free survival rates when comparing the mastectomy and BCS. In recent years, BCS has become the preffered method of treatment for many patients in our clinic. Age and use of boost radiation were important determinants of local recurrence in BCS.